Faktor Penyebab dan Upaya Perlindungan Hukum Terhadap Guru Yang Dianiaya Oleh Oknum Orang Tua Siswa di SD Negeri Naikoten II - Andi Williams Abraham; Rudepel Petrus Leo; Heryanto Amalo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Currently, the world of education can be said to be facing a crisis of value as the development of the dynamics of community life. The world of education in this era faces complex problems that can hinder the achievement of educational goals. These problems arise either because of internal factors or external factors. This study uses empirical legal research methods that examine how the law works in society. Aspects of the study examined the causes of violence committed by parents to teachers and forms of legal protection for teachers who experience violence. The results found that: (1) the factors that make the perpetrators (parents) abuse the teacher caused by lack of socialization and coordination between the school and the parents. The lack of socialization and coordination makes the perpetrators (parents) angry and emotional so they think of mistreating the teacher. Lack of accurate information that makes parents misunderstand the treatment of teachers to their children while at school that causes parents to start emotions and abuse such as beatings. (2) efforts made as a form of protection against cases of abuse against teachers by parents of students are realized through preventive actions by appealing to the public to immediately report to the authorities in the event of a crime including the crime of abuse by unscrupulous parents of students against teachers in the school environment.Suggestions from this study: (1) it is expected that the government and all related agencies in terms of improving education through schools, it is good to teach teachers with methods adapted to the current global conditions, so that teachers can better answer the challenges of the times in terms of education and the condition of students then and now is very much different. (2) expected for all parties concerned, both the police, legal aid agencies, witness and victim protection institutions of the government and the community to continue to improve cooperation in an integrated manner in tackling the occurrence of crime, especially crime cases of abuse by unscrupulous parents of students against teachers.